Plasma and vitreous homocysteine concentrations in patients with proliferative diabetic retinopathy - Aydemir, Orhan; Turkcuoglu, Peykan; Guler, Mete; Celiker, Uelkue; Ustundag, Bilal; Yilmaz, Turgut; Metin, Kerem (Lippincott Williams & Wilkins, 2008)
Purpose: An increase in plasma concentrations of homocysteine (Hcy) in proliferative diabetic retinopathy (PDR) has been described. The aim of this study was to investigate vitreous Hcy levels in patients with PDR. Methods: Plasma and vitreous samples were obtained simultaneously at the time of vitreoretinal surgery from 20 patients with PDR and 12 nondiabetic patients with nonproliferative ocular diseases. Hcy levels were determined by high-performance liquid chromatography. Results: The mean vitreous and plasma Hcy concentrations for the diabetic group were 3.64 +/- 0.65 mu mol/L and 16.04 +/- 2.75 mu mol/L, respectively. The mean intravitreal and plasma Hcy concentrations for the control group were 1.08 +/- 0.45 mu mol/L and 9.18 +/- 3.91 mu mol/L, respectively. Both plasma and vitreous Hcy concentrations for the diabetic group were significantly higher than those for the control group (P < 0.001). A statistically significant correlation between vitreous and plasma Hcy concentrations was present only for the diabetic group (r = 0.525; P = 0.017). Conclusion: Vitreous Hcy concentrations were elevated in patients with PDR probably due to breakdown of the blood-retina barrier.
Keywords: concentration; homocysteine; plasma; type 2 diabetes mellitus; vitreous